International Monetary Fund Annual Report 2014 : From stabilization to sustainable growth. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 2014)
Seven years after the onset of the global financial crisis, the world still has a way to go to secure a sustainable recovery marked by strong growth that supports rapid job creation and benefits all, International Monetary Fund (IMF) Managing Director Christine Lagarde says in her foreword to the institution's Annual Report 2014-From Stabilization to Sustainable Growth, published today. 'The recovery is ongoing, but it is still too slow and fragile, subject to the vagaries of financial sentiment. Millions of people are still looking for work. The level of uncertainty might be diminishing, but it is certainly not disappearing.' Ms. Lagarde said that 'throughout the crisis and in the recovery period, the IMF has been, and continues to be, an indispensible agent of economic cooperation' for its membership. The report covers the work of the IMF's Executive Board and contains financial statements for the year May 1, 2013, to April 30, 2014. It describes the IMF's support for its 188 member countries, with an emphasis on the core areas of IMF responsibility: assessing their economic and financial policies, providing financing where needed, and building capacity in key areas of economic policy.